Surface organization of aptamers via diazonium grafting: A key parameter in label-free electrochemical sensing - Teodora Lupoi; Bogdan Feier; Florence Geneste; Cecilia Cristea; Yann R. Leroux (Electrochemistry Communications, 2025)
The spatial arrangement of biorecognition molecules on the sensor surface plays a critical role in determining the performance of electrochemical biosensors. In this work, we report a covalent and tunable immobilization strategy using aryl diazonium chemistry to functionalize carbon electrodes with ethynyl groups protected by trimethylsilyl (TMS) or triisopropylsilyl (TIPS) moieties. After deprotection, an azide-modified aptamer (APT) specific to diclofenac (DCF) was immobilized via copper-catalyzed azide–alkyne cycloaddition (CuAAC). Although the TMS and TIPS groups differ in size by only 1.7 Å, this small variation significantly influenced APT spacing and sensor performance. The TIPS-based sensor displayed a nearly fourfold increase in signal response compared to the TMS-based counterpart, achieving a limit of detection of 17.95 μM. These results underscore the importance of nanoscale molecular design in optimizing label-free aptasensor sensitivity.